Mallory-Denk bodies: Correlation with steatosis, severity, zonal distribution, and identification with ubiquitin - Kayaçetin, Serra; Başaranoğlu, Metin (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: Intermediate filament proteins contain few aggregates as their main component. Among those, Mallory–Denk bodies (MDBs) are by far the best recognized component. To identify the presence of MDBs in individuals having chronic liver disease and to evaluate the correlation among MDBs and steatosis as well as the severity and zonal distribution of hepatocyte balloon degeneration. Tertiary reference hospital. Materials and Methods: Three hundred consecutive liver specimens derived from our patients with chronic liver disease were included in the current study. Immunohistochemistry analysis was conducted on frozen liver biopsies fixed at room temperature with acetone anti-rabbit antibody to ubiquitin. In addition, histological activity was evaluated by the routine staining of liver biopsy sections with hematoxylin–eosin and periodic staining by acid-Schiff stain, reticulin, Masson trichrome, and iron. The presence of MDBs, steatosis, severity, and the zonal distribution of hepatocyte balloon degeneration were evaluated in every patient. Results: Histopathologic diagnosis were chronic hepatitis B (n=219), alcoholic steatohepatitis (n=23), non-alcoholic steatohepatitis (n=20), chronic hepatitis C (n=20), overlap syndrome (n=10), and primary biliary cirrhosis (n=8). The distribution of MDBs stained positive for ubiquitin was 80% in the overlap syndrome, 86% in chronic hepatitis B, and 100% in alcoholic steatohepatitis, NASH, chronic hepatitis C, and primary biliary cirrhosis. There was a correlation between the severity of steatosis and ubiquitin positivity, particularly in zone 2. A conspicuous correlation existed between the severity of hepatocyte balloon degeneration and ubiquitin positivity. Conclusion: These findings have demonstrated that the observation of MDB together with ubiquitin positivity will be helpful in the evaluation of the models of diagnosis, staging, and therapy in patients with chronic liver disease.